n Vrugontwikkelingstudie van Malus domestica, Bork., cultivar Golden Delicious - Lötter, J. de V.(Jacobus de Villiers) (Stellenbosch : Stellenbosch University, 2012)
Skripsie (M. Sc. Agric.) -- Universiteit van Stellenbosch, 1965.